Chelate Silylene–Silyl Ligand Can Boost Rhodium‐Catalyzed C−H Bond Functionalization Reactions. Issue 55 (11th September 2018) - Mo, Zhenbo; Kostenko, Arseni; Zhou, Yu‐Peng; Yao, Shenglai; Driess, Matthias
Abstract: The first N‐heterocyclic silylene (NHSi)–silane scaffold LSi−R−Si(H)Mes2 (1 ) (L=PhC(N t Bu)2 ; R=1, 12‐xanthendiyl spacer; Mes=2, 4, 6‐Me3 C6 H2 ) was synthesized and used to form the unique rhodium(III) complex (LSi−R−SiMes2 )Rh(H)Cl2 through its reaction with 0.5 molar equivalents of [Rh(coe)2 Cl]2 (coe=cyclooctene). An X‐ray diffraction analysis revealed that2 has a (Si II Si IV )Rh(H)Cl core with three short Rh⋅⋅⋅ H−C contacts with Me groups of the ligand1, which cause a distorted pentagonal bipyramidal coordination of the Rh center. Unexpectedly, the reaction of2 with t BuONa gives the new bis(silyl)hydridorhodium(III) complex4 . Due to the strong donor ability of the chelate Si II –Si IV ligand, 2 and4 can act as highly efficient pre‐catalysts in the Rh‐mediated selective C−H functionalization of 2‐phenylpyridines with C−C unsaturated organic substrates under mild reaction conditions. Abstract : Agostic complexes : A pentagonal‐bipyramidal rhodium(III) complex featuring one agostic and two anagostic interactions with a new Si II –Si IV ligand has been synthesized. It can be used as pre‐catalyst for alkenylation and alkylation of C−H bonds with high catalytic efficiency under mild reaction conditions (see scheme).